Functions of the School Committee In Efforts to Improve Facilities and Infrastructure at Madrasah Aliyah Negeri 1 Banyuwangi - Fazriyati, Maswanda (Faculty of Islamic Sciences, Raden Rahmat Islamic University Malang, 2025)
Committees have an important position in educational institutions. By PMA No. 16 of 2020, school committees have functions in school improvement, namely consideration, support, and supervision. Schools rely on committees to improve school quality, especially facilities and infrastructure. Schools cannot only rely on government assistance because it is limited. So they need a committee to provide infrastructure that is not included in government assistance. The research aims to determine (1) the consideration function. (2) Support function (3) Supervisory function. Type of case study research with a qualitative approach. Data collection techniques: observation, interviews, and documentation. Data analysis techniques: data reduction, data presentation, and conclusion. Checking the validity of data using triangulation. The results of this research are (1) the committee's function is as consideration, namely consideration in setting school policies and programs, work plans and budgets, and developing facilities and infrastructure. (2) The committee has supporting functions: financially, mind, and soul in the form of energy. (3) The MAN 1 Banyuwangi Committee, as a supervisory function, carries out supervision using monitoring and evaluation and supervision periodically and at any time. Keywords: Functions of the School Committee, Improvement of Infrastructure.